Pemberantasan korupsi anggota DPRD di era otonomi daerah - Mukhamad Murdiono (Jurnal Civics: Media Kajian Kewarganegaraan, 2004)
Since the implementation of decentralization, the drastic changes of politic and governmental system has been occurred in Indonesia. One of those changes is the growing significant of legislature role. In autonomy of district era, legislature was growing to be powerful marked by the function of its role, as aspiration channel and executive controller. The empowerment of legislature role in autonomy era brings some problems, not only connected with legislature themselves but also with executive. The problem connected with legislature can be cited such as bad behaviors (manipulation of graduation, money politics, corruption, etc.). Those bad behaviors have been caused the degradation of DPRD image and decadency moral. Therefore, it is necessary to rebuild politic morality and to change the image of legislative members. In order to change the image of DPRD the things can be done are reformation and radical change of DPRD by all element of society. Besides that, it is necessary to review the relationship between DPRD and people. The members of DPRD should compromise their views as well as their own needs with the people's aspirations and needs.